Exploring Corporate Finance Dynamics: A Qualitative Study on Capital Structure, Firm Value, and Dividend Policies - Rumasukun, Mohammad Ridwan; Nochh, Muhammad Yamin (Golden Ratio of Finance Management, 2024)
This qualitative study delves into the intricate dynamics of capital structure, firm value, and dividend policies within the realm of corporate finance. The research aims to explore the factors influencing financial decision-making processes and their implications for firm performance and shareholder wealth maximization. Adopting a systematic literature review approach, the study synthesizes existing theoretical frameworks, empirical evidence, and alternative perspectives to provide a comprehensive analysis of the chosen topic. The research methodology involves data collection through academic databases and scholarly sources, followed by thematic analysis to identify recurring themes and patterns in the literature. The findings highlight the multifaceted nature of financial decision-making, challenging traditional theories such as the irrelevance theory and emphasizing the significance of alternative perspectives such as the pecking order theory, signaling hypothesis, and clientele effect. Moreover, empirical evidence suggests nonlinear relationships between capital structure, firm value, and dividend policies, indicating the influence of contextual factors such as industry dynamics, regulatory environments, and market conditions. The implications drawn from this study extend to both academia and practical applications, emphasizing the need for a nuanced understanding of corporate finance dynamics to inform theory, practice, and policy in the field. By embracing interdisciplinary perspectives, methodological pluralism, and a forward-looking orientation, researchers and practitioners can contribute to the continued evolution of corporate finance theory and practice, ultimately driving innovation, efficiency, and sustainability in the corporate sector.